Case Report: Malignant Melanoma Treated with Ipilimumab and Nivolumab in Patient with Multiple Sclerosis - Abbas, Tahir; Sundaram, Vinita (British Journal of Healthcare and Medical Research, 2025)
This case report presents a patient with relapsing and remitting multiple sclerosis (MS) and metastatic malignant melanoma treated with combination immunotherapy. Ipilimumab and nivolumab was tolerated with no significant adverse events. There was no progression of multiple sclerosis while she received immunotherapy. This demonstrates that Ipilimumab and nivolimumab can be considered in patients with pre-existing multiple sclerosis requiring treatment with checkpoint inhibitors, but should have close multidisciplinary monitoring.